TARAKAN STRUCTURAL MODEL OF IMPLEMENTATION OF THE PREFERENCE PROGRAM CITY GAS UNDER ANY THEORY OF PLANNED BEHAVIOUR - Haryono, Tubagus; Sumarwan, Ujang; Saefuddin, Asep (European Scientific Journal, ESJ, 2013)
Oil and Gas play very important role in Indonesian Economy as a source of domestic energy, feedstock for national industry and source of government income. Therefore the government of Indonesia through Law No. 22 of 2001 and Presidential Regulation No. 5 of 2006 trying to utilize alternative energy to reduce fuel subsidies including the utilization of natural gas. To support the government’s plan, this study need to formulate the strategy of the Gas City development in Indonesia by identifying the factors that influence consumer’s perceptions, attitudes and intentions in using natural gas, which refers to the model proposed by Icek Ajzen (1991) which is known as The Theory of Planned Behaviour. Based on statistic examination toward γ parameter (Gamma) are able to conclude that there is a positive and significant influence from attitude toward behaviour, power of controlling behaviour factor and perceived risk toward the intention to use gas. But the attitude toward behaviour, give the most influence for decision. Trust to control of power factor give a positive and significant influence, and it happened to trust toward perceived risk. But subjective norm toward intention bring a negative influence. In addition to, the demography factor is including a significant factor in forming respondent decision for using natural gas. The respondent in higher economic status, have more independent opinion (attitude toward behaviour, the consequence evaluation, control beliefs, power of control behaviour) to determine using or not using natural gas. The suggestion which come from government and most of user is turn out them to influence using the natural gas. Likewise to the respondent in middle and low economic status but they still also have been thinking about the perceived risk that might be come when using the gas.